Beauty IN Al- Kindi - Ali, Hanan Majeed (Al-Adab Journal, 2021)
Al- kindi did not write a special book to study the topic of beauty, but it is the first music of great importance due to its great influence on the emotions of the soul and its tendency if most of his aesthetic views came within his musical compositions Al-kindi did not write a specific book to address beauty, however he allocated special importance to music due to its great impact on the emotions. therefore, most of his aesthetic views were included in his musical compositions. Al-kind indicated that the aesthetic taste is changeable and differs from one person to another due to the different weather and social conditions. Al-kindi defines the aesthetic taste as a sensual process that depends on the impact of aesthetic works on our souls through their effects on our feelings and emotions. Furthermore, al-kindi stresses that music is the art that is the closest to the spiritual aspect because the sense of hearing is the closest to the inner self and more field to the inner world of humans than the other senses.